2023
DOI: 10.1002/ajmg.c.32058
|View full text |Cite
|
Sign up to set email alerts
|

Development of webcam‐collected and artificial‐intelligence‐derived social and cognitive performance measures for neurodevelopmental genetic syndromes

Thomas W. Frazier,
Robyn M. Busch,
Patricia Klaas
et al.

Abstract: This study focused on the development and initial psychometric evaluation of a set of online, webcam‐collected, and artificial intelligence‐derived patient performance measures for neurodevelopmental genetic syndromes (NDGS). Initial testing and qualitative input was used to develop four stimulus paradigms capturing social and cognitive processes, including social attention, receptive vocabulary, processing speed, and single‐word reading. The paradigms were administered to a sample of 375 participants, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…While many SYNGAP1-ID participants had difficulty with the calibration process, as well as maintaining attention and interest throughout the task, we nevertheless successfully managed to obtain data from these participants. The possibility of remote eye tracking, which could be done via a tablet or remote webcam software in the participants own home, may help in future to improve inclusion numbers (Frazier et al, 2023). In addition, creating more tailored tasks to individual interests, although introducing variability, may allow a greater retention of participants and thus allow for more meaningful conclusions to be extracted about this group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many SYNGAP1-ID participants had difficulty with the calibration process, as well as maintaining attention and interest throughout the task, we nevertheless successfully managed to obtain data from these participants. The possibility of remote eye tracking, which could be done via a tablet or remote webcam software in the participants own home, may help in future to improve inclusion numbers (Frazier et al, 2023). In addition, creating more tailored tasks to individual interests, although introducing variability, may allow a greater retention of participants and thus allow for more meaningful conclusions to be extracted about this group.…”
Section: Discussionmentioning
confidence: 99%
“…Eye tracking has been used to examine social differences in autism more broadly, but there has only been a limited investigation into these skills for those with SYNGAP1-ID. The only SYNGAP1-ID eye tracking study to date to examine social attention showed that these individuals demonstrated significant reductions in overall attention, attentional scanning, social attention and slower speed to faces and objects, as well as increases in nonsocial preference relative to typically developing controls (Frazier et al, 2023). In regards to ASD, metaanalytic findings of social attention in ASD have revealed that individuals with ASD spend less time looking at social stimuli (Chita-Tegmark, 2016) with this most affected for stimuli that had a high social content (e.g., showing more than one person (Chita-Tegmark, 2016)).…”
Section: Introductionmentioning
confidence: 99%